TQM engineering handbook - Stamatis, D.H (Marcel Dekker, 1997)
This practical resource establishes a sound rationale for the continuation of Total Quality Management (TQM) in all organizations, offering a model and an implementation strategy, as well as traditional and nontraditional methods for the successful enhancement and maintenance of quality. Providing self-contained chapters as well as references, tables, equations, and drawings, TQM Engineering Handbook is an excellent guide for quality managers and engineers; statisticians; executives, supervisors, facilitators, and marketing and sales managers, and graduate-level students in these disciplines.